The Religious Spirituality in a Time of Pandemic; Strategies for Strengthening Diversity in FIS UNJ Students - Afif Ridho Pramudya; Muslimatun Kholifah Anta; Hana Taqiyya; Muhamad Ridwan Effendi (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2021)
The presence of the Covid-19 virus in various parts of the world, including Indonesia, has limited various movements and activities, including worship. The MUI has ijtihad by issuing a fatwa regarding the implementation of worship during the Covid-19 pandemic. However, it reaps the pros and cons. This phenomenon is the object of this study. This study intends to describe the religious attitudes of PAI FIS UNJ students in the midst of the 2019 corona virus disease (COVID-19) outbreak. The research method in this journal is a quantitative survey research method. Which is used to collect information from a group of people in order to describe aspects of the research. From the survey results to PAI FIS UNJ students, it was concluded that there were pros and cons regarding the fatwa issued by the MUI. Overall, they did not experience difficulties in worshiping during the pandemic and the majority of PAI FIS UNJ students agreed with the MUI fatwa even though there were some suggestions for the fatwa. Actually, the main problem that occurred was the pros and cons of PAI FIS UNJ students regarding the implementation of worship, namely the existence of misunderstandings in responding to the results of the fatwa of the Indonesian Ulema Council (MUI). So, we need to look more carefully and really understand the fatwa issued by the MUI.